A compact slotted microstrip patch antenna for RFID applications - Mokhtar, Muhammad Hazmi (2013)
This paper presents a compact slotted microstrip patch antenna for RFID applications. The antenna is designed to operate at 2.40-2.45 GHz using the Computer Simulation Technology (CST) software. The proposed antenna is designed and fabricated using Flame Retardant 4, FR4 substrate with the design specification dielectric constant (er) of 4.5 and thicknesses (d) of 1.6mm. In order to minimize the size of the microstrip patch antenna, the proposed antenna contains additional slotted structure attached in the reflector of FR-4 substrate. The new Compact Slotted Microstrip Patch Antenna (CSMPA) reduce by 50% from its conventional size for 2.40 GHz microstrip antenna operated frequency antenna. The antenna produces gains of 2.5 dB at 2.415 GHz with the overall size of antenna about 35 × 26 × 1.67 mm. Simulation and optimization of the presented CSMPA produced a good results which suitable for RFID applications.